Nilai-Nilai Islam dalam Budaya dan Kearifan Lokal (Konteks Budaya Bugis) - Abd Rahim Yunus (Universitas Islam Negeri Alauddin Makassar, 2015)
The aim of this essay is to analyze the influence of Islamic value in culture and local wisdom of Buginese people. Then we will find a tremendous fact, that our culture and local wisdom has an Islamic value. Talking about culture, culture is something very important in a society, because culture is an identity. Culture makes a society different with the other society. In a society, culture has a value, but it different in every societies, because it is influence by society background. Indonesian culture is different with Arabic culture. Arabic culture influnce by desert, so they live in hard life, that is completely different with Indonesian life because they live in fertile area. Fertile area will create a tremendous culture, namely local wisdom. Local wisdom in a society could influenced by religion. In Indonesia, local wisdom was influenced by Islamic value. It happened, since Islam had becomed a majority that influenced every people in our society. Further, Indonesian had a local wisdom than it was combined with Islam, especially Islamic value. It made a culture has Islamic value.